Analysis of Consistency of Volleyball Top Serve of Sports Coaching Education Students, Faculty of Sport Science, State University of Malang in Indoor Volleyball Games - Muhammad Atiq Noviudin Pritama; Prisca Widiawati; Rizqie Putri Novembriani; Muhammad Isna Nurdin Wibisana (Indonesian Journal of Sport Management, 2025)
Consistency in service skills is crucial for athlete development and performance. This study evaluated the consistency of overhand serve skills in volleyball among students in the Sports Coaching Education program at the Faculty of Sport Science, State University of Malang, focusing on indoor volleyball. The descriptive method was employed to gather data using the AAHPER Youth Fitness Test. The findings indicated that most participants exhibited moderate to low proficiency in volleyball overhand serving performance, with 39.44% classified as "Fair" and 33.10% as "Poor." The average performance score was 2.45, with a standard deviation of 0.97, signifying considerable range in students' skill levels. These findings suggest that students' consistency in volleyball overhand service skills is still evolving and highlight the necessity of integrating theoretical knowledge with practical execution. A well-organized curriculum enhances training consistency, communication proficiency, and player involvement. This research significantly contributes to coaching education by highlighting the necessity of practice-based learning methodologies to enhance volleyball serve proficiency, adequately prepare future coaches, and ultimately elevate athlete performance in competitive environments.